Utilization of Forest Plants as Spices by Women in Benua Kencana Village, Sintang - Gusti Eva Tavita; Yeni Mariani; Ellen Putri Yumita; Yusro, Fathul (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Spices have many benefits, especially as additional ingredients in cooking, traditional medicine and raw materials for the pharmaceutical and cosmetic industries. This study aims to identify forest plant species utilized as spices by women in Benua Kencana Village, Sintang Regency, and to understand their usage and processing practices. The research employed a survey method with semi-structured interviews involving 161 female respondents. Data analysis was conducted using Use Value (UV) and Fidelity Level (FL) to assess the degree of utilization and community trust in forest spice plants. The results indicate that the utilized plant parts include leaves, stems, fruits, and bark, serving various functions such as flavor enhancers (sweet, sour, and aromatic), tenderizers, preservatives, and neutralizers in cooking. The plants with the highest UV values (1.00) were Garcinia xanthochynus (asam kandis) and Pycnarrhena cauliflora (sengkubak), while those with the highest FL values (100%) included Pycnarrhena cauliflora (sengkubak), Eryngium foetidum (sumpak laut), Garcinia xanthochynus (asam kandis), Baccaurea motleyana (rambai), and Baccaurea angulata (benit). Women play a dominant role in the management and utilization of these spices, particularly in selecting, processing, and passing down knowledge about their uses. This study highlights the importance of documenting and preserving local knowledge to support food security and the conservation of natural resources.